Théâtre et presse, de 1590 à 2017 - Michael Palmer (Communication)
The author examines British plays written since 1626 that satirize the news and, in passing, the press, news writers, and journalists. Dramatic works for radio and television are not included in the corpus. He occasionally refers to the context in which the plays were produced and concludes with a question as to why, in recent decades, French playwrights have neglected the press as a theme in their works.